Community business impacts on health and well-being: a systematic review of the evidence. Issue 3 (9th June 2021) - McClean, Stuart; Ismail, Sanda; Bird, Emma
Abstract : Purpose: This paper aims to provide critical insight into the impact of locally embedded, community business-related approaches internationally to health and social care on users' outcomes, in particular exploring their effectiveness in delivering outcomes for users. Design/methodology/approach: The study used a robust systematic review methodology. It carefully identifies relevant studies that have been conducted on the impact of community business-related approaches, rigorously evaluates how well these studies have been carried out and combines the results from these studies to address that particular topic. Findings: Health and social care-related community businesses deliver on a range of health and well-being outcomes and impacts positively on local residents' satisfaction with their community/local area. Existing research into community businesses uses mostly qualitative methods, but a few studies have also used quantitative survey and mixed methods and demonstrate the challenges of conducting methodologically rigorous real-world research within local community settings. Research limitations/implications: The review was limited to papers published in English language and may have missed relevant studies published in other languages which could have influenced the overall findings. Only one reviewer screened the titles and abstracts of the identified papers. Having multiple reviewers would have strengthened the validity of the screening process. Originality/value: Community businesses offer a positive contribution to health and well-being, and highlight the significance of engaging local communities in promoting health, reducing health inequalities and addressing the wider determinants of health. This paper provides a baseline of evidence about community business' broad impacts on health and well-being to help inform new and emerging evidence